2015
DOI: 10.1109/jcn.2015.000102
|View full text |Cite
|
Sign up to set email alerts
|

Big data meets telcos: A proactive caching perspective

Abstract: Mobile cellular networks are becoming increasingly complex to manage while classical deployment/optimization techniques and current solutions (i.e., cell densification, acquiring more spectrum, etc.) are cost-ineffective and thus seen as stopgaps. This calls for development of novel approaches that leverage recent advances in storage/memory, context-awareness, edge/cloud computing, and falls into framework of big data. However, the big data by itself is yet another complex phenomena to handle and comes with it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 36 publications
0
85
0
Order By: Relevance
“…[68] Suggested monitoring and analyzing social media and popular sites, to predict and cache certain contents, according to age category, at the predicted locations where these contents are highly demanded. [34] Proposed the use of big data analytics and machine learning techniques to proactively cache popular content in 5G networks. Network optimization [73] Presented three case studies in which a proposed network optimization framework is efficiently utilized.…”
Section: Signaling Data-based Intelligent Lte Network Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[68] Suggested monitoring and analyzing social media and popular sites, to predict and cache certain contents, according to age category, at the predicted locations where these contents are highly demanded. [34] Proposed the use of big data analytics and machine learning techniques to proactively cache popular content in 5G networks. Network optimization [73] Presented three case studies in which a proposed network optimization framework is efficiently utilized.…”
Section: Signaling Data-based Intelligent Lte Network Optimizationmentioning
confidence: 99%
“…An approach, proposed by the authors in [34] , used big data analytics and machine learning to develop a proactive caching mechanism by predicting the popularity distribution of the content in 5G cellular networks. They demonstrated that this approach can achieve efficient utilization of network resources (backhaul offloading) and an enhanced user experience.…”
Section: Proactive Caching In 5g Networkmentioning
confidence: 99%
“…As a matter of fact, the popularity of requested contents follows the Zipf's distribution [23][24][25], which can be expressed as:…”
Section: Wireless Transmission and Content Caching Modelmentioning
confidence: 99%
“…Like the distribution of contents in the web proxies and the traffic dynamics of cellular devices, this kind of power law is used to characterize many real world phenomena [23]. The higher α value corresponds to a steeper distribution, and indicates that a fraction of the content is more popular than the rest of the catalog (i.e., users have very similar interests).…”
Section: Wireless Transmission and Content Caching Modelmentioning
confidence: 99%
“…The first paper to propose the idea to use machine learning to learn caching rules from available rich data was probably [2]. Nevertheless, the only practical example considered there was collaborative filtering to estimate content popularities at some locations from measurements at other locations.…”
Section: Introductionmentioning
confidence: 99%